IDNLearn.com is your reliable source for expert answers and community insights. Ask your questions and receive detailed and reliable answers from our experienced and knowledgeable community members.

Use the Distributive Property to solve the equation. 4x - 2(x - 3) = -4 + 5x - 5

Sagot :

Answer:

x=5

Step-by-step explanation:

First, open up the parentheses to get 4x-2x+6=-4+5x-5. Now, move all numbers without variables to the right and those with variables to the left to get 4x-2x-5x=-4-5-6. Simplify both sides to have -3x=-15. Now divide both sides by -3 to get x=5